PENGEMBANGAN MEDIA EDUCAPLAY UNTUK MENINGKATKAN MUFRODAT SISWA DI SEKOLAH DASAR - nunik Zuhriyah; Yulin Nada; M Zunaidul Muhaimin (Al-Muttaqin : Jurnal Studi, Sosial, dan Ekonomi, 2025)
Education play is a website-based learning platform used to create educational games that can be used interactively by teachers and students. This research aims to develop game-based interactive learning media through the EducaPlay platform to improve students' Arabic language skills at Elementary Schools . The research method used is Research and Development (R&D) with the ADDIE development model (Analysis, Design, Development, Implementation, Evaluation). The object of research was taken from class V students of MI Bustanul Mu'min Kediri with a total of 20 students. Data collection methods using observation, interviews, documentation, questionnaires and tests. The results of this study show that the EducaPlay game is effective in improving students' Arabic language skills with a significant increase in learning outcomes after using this media. Product Desain validation on educaplay game learning media is 89% with a valid category, while the material validation is 84%.